2021
DOI: 10.3917/inka.211.0005
|View full text |Cite
|
Sign up to set email alerts
|

Création d’une unité spécifique de soins palliatifs dans un service d’urgences en période de pandémie : étude descriptive qualitative

Abstract: Infirmière spécialiste clinique en antalgie et soins palliatifs, Direction des soins, Hôpitaux universitaires de Genève (HUG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In addition, the ICPs reported that, at the beginning of the crisis, there was teamwork and a positive relationship between colleagues. Elsewhere, cohesion and team spirit were reported as essential elements to working together [75]. The recognition of work accomplished, the development of medical knowledge, and the reinforcement of professional skills are also two motivating factors intrinsically linked to work [76].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ICPs reported that, at the beginning of the crisis, there was teamwork and a positive relationship between colleagues. Elsewhere, cohesion and team spirit were reported as essential elements to working together [75]. The recognition of work accomplished, the development of medical knowledge, and the reinforcement of professional skills are also two motivating factors intrinsically linked to work [76].…”
Section: Discussionmentioning
confidence: 99%